Challenges and Opportunities of AI Implementation in Financial Sector Early Warning System - Judijanto, Loso; Suwandi Tjeng, Prastika; Nopianti, Rina (International Journal of Social Science, Education, Communication and Economics, 2025)
Digital transformation in the financial sector encourages the adoption of Artificial Intelligence (AI) in early warning systems to improve the effectiveness of risk detection and mitigation. This study aims to identify and analyse the challenges and opportunities of AI implementation in the financial sector early warning system through the literature review method. The results show that AI offers great opportunities in improving fraud detection accuracy, operational efficiency, service personalisation, and data-driven decision making. However, AI implementation also faces significant challenges, such as data quality and security issues, risk of algorithm bias, limited human resources, and the need for adaptive regulation and governance. Optimising these opportunities and mitigating these challenges requires a comprehensive strategy that includes strengthening data governance, improving cybersecurity, developing human resources, and collaborating with regulators. With the right approach, AI can be a key foundation in strengthening the resilience and competitiveness of the financial sector in the digital era.